Sustainable Green Economy for a Supply Chain with Remanufacturing by Both the Supplier and Manufacturer in a Varying Market - Rimi Karmakar; Sanat K. Mazumder; Md Billal Hossain; Csaba Balint Illes; Arindam Garai (Logistics, 2023)
Background: In a typical multiechelon supply chain, the supplier makes semifinished items, from which the manufacturer produces finished products to eventually get sold at retailers. However, the majority of existing supply chain models consider the remanufacturing of defective products by solely one organization, despite the fact that both the supplier and manufacturer can produce defective products. This study considers the remanufacturing of defective products with fresh materials and additional expenses by both the supplier and manufacturer. Contrary to well-established articles that hold major partners to be accountable for reducing carbon emissions under a carbon cap-and-trade policy, the proposed model presumes an initial green technological investment by each chain partner. Methods: This study represents a varying market with fuzzy cost components that are then defuzzified with <semantics>λ</semantics>-integral method. This study determines the critical values of three discrete and four other continuous decision variables that globally maximize the profitability of the proposed model. Results: Slower production with a longer cycle boosts profitability in a developing market. To increase profit, a case study on the oil and natural gas business suggested to reduce the production of defective items and cutting emission through green investments. Conclusions: Managers can sustainably boost profit via careful production, modern machinery, and slightly longer cycles.